Tratamento da migranea refratária na unidade de emergência do complexo hospitalar de Barbacena – REDE FHEMIG - Andrade, Priscilla Garcia de (Headache Medicine, 2024)
Headache is one of the primary neurological complaints in emergency departments. It is not uncommon for headachesto persist even with appropriate treatment. The initialevaluation should differentiate between primary andsecondary headaches, determine the need for furtherinvestigation, and treat the acute pain. Migraines, in particular, are among the most disabling primaryheadches, affecting quality of life and burdening thehealthcare system. Refractory migraine is characterized bythe lack of response to standard preventive and acutetreatment, requiring a more aggressive therapeuticapproach.The objective of the study is to evaluate the therapeuticresponse in the treatment of refractory migraine at theEmergency Department of the Barbacena Hospital Complex, two hours after the administration of a combination of 5 mg of intravenous or oral haloperidoland intravenous or oral dexamethasone in patientsclassified as refractory to initial treatment.The study was conducted as a prospective observationalstudy with patients considered refractory to initialmigraine treatment. Patients who did not respond to atleast three adequate dose medications were included. Afterobtaining consent, demographic data and medical histories were collected, and patients completed the Visual AnalogScale (VAS) to quantify pain. They received 5 mg ofhaloperidol (oral or intravenous) and 4 mg ofdexamethasone (oral or intravenous). After two hours, pain intensity was reassessed and quantified.The study is ongoing, with data collection from August 1, 2023, to July 31, 2024. However, with the endapproaching, it is now possible to evaluate the results andclarify the proposed objective. Currently, there are 16 patients, 15 females and 1 male, with an average age of 28 years. The results are favorable, showing improvementafter therapy by at least 2 points on the VAS and a maximum of 10 points, with only one result indifferent tothe treatment.The combination of haloperidol and dexamethasoneappears promising in treating patients who do not respondto conventional therapy, providing significant pain relief. This approach can reduce patient morbidity and healthcare costs. Additional studies are needed to optimize the doses and combinations of these medications to maximize efficacy and minimize risks.